Annotation and characterization of immunoglobulin loci and CDR3 polymorphism in water buffalo (Bubalus bubalis) - Deng, Yunlan; Wu, Fengli; Li, Qianqian; Yao, Lidie; Yang, Chengzhi; Ma, Long; Yao, Xinsheng; Li, Jun (Frontiers in Immunology, 2025)
IntroductionImmunoglobulin (Ig) refers to the nomenclature for all antibody proteins produced by B lymphocytes. The genetic locus encoding Ig is critical for vertebrate humoral immune responses and diverse antibody repertoires. Despite the critical role of buffaloes as livestock and their significance in disease transmission, the Ig loci of this species have not been thoroughly annotated. This study aimed to systematically characterize the Ig loci in buffaloes and their unique features, providing a foundation for understanding buffalo immune function.MethodsThe genomic assembly of Murrah buffalo (NDDB_SH_1) was analyzed to annotate Ig loci. Annotation criteria included functional motifs, RSS sequences, and structural features of V, D, J, and C genes. The CDR3 repertoires were constructed using genomic DNA extracted from spleen samples of five healthy buffaloes. High-throughput sequencing of multiplex PCR products enabled repertoire analysis, and MiXCR software was used for alignment and CDR3 extraction. Repertoire diversity, gene usage, and clonal frequencies were analyzed using the Immunarch R package.ResultsThe IgH locus spans approximately 667 kb on chromosome 20, containing two D-J-C clusters, 54 VH genes, 10 DH genes, 8 JH genes, and 9 CH genes. The Igκ locus, located on chromosome 12, encompasses 24 Vκ genes, 5 Jκ genes, and 1 Cκ gene, while the Igλ locus on chromosome 17 includes 71 Vλ genes, 3 Jλ genes, and 3 Cλ genes. We also conducted a detailed examination of the buffalo IgH CDR3 repertoire, revealing the presence of ultra-long CDR3 sequences, a biased usage of certain V genes, and a high-frequency usage of IgHJ1-4 genes. Furthermore, we identified a set of shared clonotypes across the samples, highlighting commonalities in the buffalo antibody repertoire.ConclusionThese findings contribute to the understanding of buffalo immune function and provide insights into the evolution and diversity of ruminant immunoglobulin genes.